2019
DOI: 10.1016/j.jctube.2019.100122
|View full text |Cite
|
Sign up to set email alerts
|

Quality of TB care among people living with HIV: Gaps and solutions

Abstract: Tuberculosis (TB) is the leading infectious cause of death among people living with HIV, causing one third of AIDS-related deaths globally. The concerning number of missing TB cases, ongoing high TB mortality, slow reduction in TB incidence, and limited uptake of TB preventive treatment among people living with HIV, all indicate the urgent need to improve quality of TB services within HIV programs. In this mini-review we discuss major gaps in quality of TB care that impede achieving prevention and treatment ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 76 publications
(105 reference statements)
0
20
0
Order By: Relevance
“…20,21 Given the substantial contribution of PPM-1, 13 and the large estimates of community pharmacies providing TB medications without prescription, 14 a possible way to increase TB case detection rates and guideline-adherent TB care offered at private facilities may be to bring community pharmacies into the folds of the PPM-1 model. 22 Based on this rationale, we designed a study to enhance the early case detection of missing TB cases within the Pakistani healthcare system by involving private pharmacies with private general practitioners and laboratories (conventional PPM-1) in a novel approach (PPM-1 boosted). The mechanism of operation of this novel model was the development of a formalized referral pathway for patients seeking TB care at pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Given the substantial contribution of PPM-1, 13 and the large estimates of community pharmacies providing TB medications without prescription, 14 a possible way to increase TB case detection rates and guideline-adherent TB care offered at private facilities may be to bring community pharmacies into the folds of the PPM-1 model. 22 Based on this rationale, we designed a study to enhance the early case detection of missing TB cases within the Pakistani healthcare system by involving private pharmacies with private general practitioners and laboratories (conventional PPM-1) in a novel approach (PPM-1 boosted). The mechanism of operation of this novel model was the development of a formalized referral pathway for patients seeking TB care at pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to healthcare engagement at each stage of the HIV/TB cascade of care impact the quality of care and can adversely affect all outcomes, including mortality. 20 A systematic review found that the main factors that affected initial engagement by Indian patients with TB care were not recognizing symptoms as severe enough to seek medical attention, work pressure, dissatisfaction with nearby health facility, lack of proximity to a healthcare facility, financial constraints, alcohol dependence, and inconvenient working hours. 21 A systematic review reported that barriers to healthcare engagement among Ethiopian presumptive TB patients included short duration of cough, absence of previous TB treatment history, lack of money, old age, low education level, lack of jobs, perceived wellness, and use of traditional healers.…”
Section: Challenges That Drive Tb-related Mortality In Plhivmentioning
confidence: 99%
“… 23 Barriers to healthcare engagement such as stigma are often intersectional and compounded in PLHIV compared with people without HIV (dual stigma for people with HIV/TB co-infection), and also highlight broader health system weaknesses, such as inefficient care delivery processes, gaps in data communication, and infrastructure. 20 …”
Section: Challenges That Drive Tb-related Mortality In Plhivmentioning
confidence: 99%
See 2 more Smart Citations